2008
DOI: 10.1002/jcaf.20388
|View full text |Cite
|
Sign up to set email alerts
|

Expatriates: Reducing failure rates

Abstract: fe a t u r e a r t i c l e 75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 7 publications
0
41
0
1
Order By: Relevance
“…Besides, a study by Neelankavil et al (2000) has identified that, culture has played significant roles in managerial effectiveness. In addition, environment and sociological examination indicated that intercultural relationship building is depend on an individual's ability to fit-in with socio-cultural setting, especially in their international travelling (Bhanugopan and Fish, 2006;Bowman and Meacheam, 2000;Forster, 1997;Harzing, 1995;Rockstuhl, 2008, 2009;Yeaton and Hall, 2008). Insensitivity to the cultural influences ruins the interpersonal relationship, the effectiveness of marketing strategies (see, Acar et al, 2011) and affect a critical emotional reaction (Awang-Rozaimie, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, a study by Neelankavil et al (2000) has identified that, culture has played significant roles in managerial effectiveness. In addition, environment and sociological examination indicated that intercultural relationship building is depend on an individual's ability to fit-in with socio-cultural setting, especially in their international travelling (Bhanugopan and Fish, 2006;Bowman and Meacheam, 2000;Forster, 1997;Harzing, 1995;Rockstuhl, 2008, 2009;Yeaton and Hall, 2008). Insensitivity to the cultural influences ruins the interpersonal relationship, the effectiveness of marketing strategies (see, Acar et al, 2011) and affect a critical emotional reaction (Awang-Rozaimie, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wirksame Ansätze und Lösungen in Bezug auf die Motivation und die Bindung der lokalen Mitarbeiter (host country subordinates) in der Expatriate-Führungssituation fehlen jedoch bisher (Templer 2010; Yealton/ Hall 2008). Die lokalen Mitarbeiter des Gastlandes (host country), die einen zentralen Erfolgsfaktor zur Erreichung der Unternehmensziele darstellen, werden somit von den Unternehmen vernachlässigt.…”
unclassified
“…The conclusion of an assignment and the transfer of the employee and his/her family back to the organization and to the home culture are often preceded by moments of high anxiety. The situation is often aggravated due to the fact that many corporations do not have policies and procedures to prepare for the return of expatriates and also do not understand the repatriation time as an important period of the cycle of the international assignment (Yeaton & Hall, 2008).…”
mentioning
confidence: 99%
“…In many cases, the knowledge acquired by the expatriate manager does not widely circulate among stakeholders at the headquarters organization once the manager returns home from the assignment (Stroh, Gregersen, & Black, 2000). The repatriation phase is often a period of high stress for returning expatriates and their families; it is estimated that between 20% and 50% of returning employees leave the corporation within one year of their return to the home country (Yeaton & Hall, 2008).…”
mentioning
confidence: 99%